2014
DOI: 10.1002/pros.22924
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofE. coli-induced prostatic inflammation on expression of androgen-responsive genes and transforming growth factor beta 1 cascade genes in rats

Abstract: Background Prostatic inflammation is reportedly associated with the development of prostatic hyperplasia. We investigated the effects of prostatic inflammation on expression levels of androgen-responsive genes and growth factors in the rat prostate. Methods Prostatic inflammation was induced by Escherichia coli (strain 1677) injection (0.2 mL of 1 × 108 CFU/mL) into the prostatic urethra of male Sprague-Dawley rats, and ventral lobes of the prostate were harvested on day 84. Rats were given 10 mg/kg celecoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
(74 reference statements)
2
13
0
Order By: Relevance
“…According to Pan et al, COX‐2 selective anti‐inflammatory agents, such as celecoxib, may be powerful inhibitors of AR expression and functions in prostatic tumor cells. More recent studies corroborated the positive correlation between COX‐2 and AR levels during inflammation and also showed the upregulation of androgen‐responsive genes in this milieu, whereas celecoxib treatment was capable of reversing these effects . Our research group has also registered such celecoxib‐dependent anti‐androgen actions and showed that AR immunolabeling and protein expression were reduced following earlier celecoxib treatment in TRAMP mice from 8 to 12 weeks old .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…According to Pan et al, COX‐2 selective anti‐inflammatory agents, such as celecoxib, may be powerful inhibitors of AR expression and functions in prostatic tumor cells. More recent studies corroborated the positive correlation between COX‐2 and AR levels during inflammation and also showed the upregulation of androgen‐responsive genes in this milieu, whereas celecoxib treatment was capable of reversing these effects . Our research group has also registered such celecoxib‐dependent anti‐androgen actions and showed that AR immunolabeling and protein expression were reduced following earlier celecoxib treatment in TRAMP mice from 8 to 12 weeks old .…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, nintedanib has shown ability to inhibit early intracellular signaling induced by TGF‐β and other TGF‐β‐activated non‐canonical pathways that also contribute to myofibroblast differentiation in this disease setting . In parallel, celecoxib also displayed antagonistic actions on TGF‐β signaling and expression during colorectal cancer and prostatitis . In different rodent models of prostatic inflammation, both TGF‐β reactivity and the expression of TGF‐β and its downstream cascade genes were decreased in the stroma following celecoxib administration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies revealed that TGF-β can activate AR in the absence of DHT and, as we show here in osteoblasts, it can cooperate with and enhance AR activation in response to DHT (Yang et al, 2014). Finally, within the context of inflammation, there are significant changes in the expression of both AR dependent and TGF-β dependent genes by prostate cells, perhaps leading to hyperplasia in that tissue (Funahashi et al, 2015). Local PGE2 levels are likely to be high in the inflamed prostate, and these findings may there relate at least in part to the individual and combined interactions that we note in our current study.…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…Since high expression of ELL2 has been reported in the prostate (Uhlen, et al 2005), ELL2 may be important for prostate homeostasis. ELL2 was also found to be an androgen response gene (Nelson, et al 2002; Bolton, et al 2007) that is up-regulated in response to chronic prostatic inflammation in rats (Funahashi, et al 2015) and was up-regulated in human benign prostatic hyperplasia (BPH) (O’Malley, et al 2009). The specific role of ELL2 in the prostate has not been fully elucidated; however, transfected ELL2 protein has been shown to interact with the potential prostate tumor suppressor gene ELL-associated factor 2 (EAF2) (Simone et al 2003).…”
Section: Introductionmentioning
confidence: 99%